PENGARUH PENGGUNAAN WEBSITE “TAN TERHADAP KEMAMPUAN PENGUASAAN KANJI PADA PEMBELAJARAN JARAK JAUH : PENGARUH PENGGUNAAN WEBSITE “TANOSHIIJAPANESE.COM” TERHADAP KEMAMPUAN PENGUASAAN KANJI PADA PEMBELAJARAN JARAK JAUH - Karyati, Alo (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2024)
This research discusses the influence of using the website "tanoshiijapanese.com on the ability to master kanji. At the beginning of 2020 a virus emerged that shocked the whole world, namely the corona virus. This virus first appeared in the city of Wuhan, China in December 2019. However, this virus quickly spread throughout the world and attacked all lines or sectors, such as: Education, economy, health, trade and others. One of the sectors that is greatly affected by this virus is education. This sector is one of the toughest apart from the health sector. Because more and more people are being exposed to this virus, all heads of state around the world are changing the learning system from face-to-face to online. The formulation of the problem in this research is: (1) Can the use of the website "tanoshiijapanese.com" improve students' writing skills during distance learning?, (2) Can the use of the website "tanoshiijapanese.com" improve students' writing skills during learning? remotely? The objectives of this research include: (1) Does the website "tanoshiijapanese.com" improve your ability to write kanji during distance learning? (2) Do you know that the website "tanoshiijapanse.com" can improve your ability to read kanji during distance learning? The research method used in this research is quantitative desktop, the population and sample in this research are 22 students from the Japanese language and culture study program at Darma Persada University, Jakarta. From this research, the results were obtained that the website "tanoshiijapanese.com" can improve writing and reading skills during online/distance learning.